Psychological Attitude of Students to Information and Computer Learning Environments - N L Sungurova (Peoples' Friendship University of Russia (RUDN University), 2013)
The article analyses the psychological phenomenon of the attitude to the computer, the results of an empirical study of the attitude of students to information and computer learning environments.